TUGAS HUKUM ENERGI DAN SUMBER DAYA MINERAL Penegakan Hukum Dalam Sektor Pertambangan Ilegal: Kasus Putusan Nomor 14/PID.B/LH/2019/Pn/Drh - Bintang Bintang; Fachrudin Iman Santoso; Fraditya Regista Putri; Imas Ratu Bilqis; Chaterine Stevanie, V. H.; Vivi Aulia (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This study examines law enforcement efforts against illegal mining activities in Indonesia, particularly in the case of cinnabar mining without a valid permit. Illegal mining poses significant environmental and economic challenges, as it results in severe ecological damage and loss of state revenue due to a lack of royalties from unregulated operations. The study highlights the urgent need for effective governance and oversight in the mining sector, emphasising that the rapid growth of illegal mining activities reflects a combination of weak regulatory enforcement, inadequate public awareness, and economic pressures faced by local communities. The court's decision in the case under review resulted in substantial prison sentences and fines for the violators, underscoring the legal consequences of illegal mining. The findings advocate a collaborative approach that engages communities in understanding environmental protection and legal compliance, which is essential for reducing illegal mining practices and ensuring sustainable resource management in the future.